2021
DOI: 10.37398/jsr.2021.650607
|View full text |Cite
|
Sign up to set email alerts
|

5-(4-chlorophenyl)-1H-tetrazole as an effective corrosion inhibitor for mild steel used in oil and natural gas industries

Abstract: The effect of 5-(4-chlorophenyl)-1H-tetrazole (Cl-PTZ) on corrosion inhibition of mild steel in 1M HCl was investigated by weight loss measurement, open circuit potential(OCP), potentiodynamic polarization and surface measurements. Results showed that the inhibition efficiency increased with increase in concentration of inhibitor and attained the maximum value at 500 ppm concentration. Polarization study revealed that 5-(4chlorophenyl)-1H-tetrazole acted as mixed-type inhibitor. Among the several tested isothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…There was also a decrease in the oxygen content, but it was not as significant as the chlorine content, this can be attributed to the fact that the used inhibitor contains oxygen moiety that can get adsorbed on the metal surface. This proves that the used inhibitors protect the mild steel sample from the corrosive media [22,23,25].…”
Section: Edax Analysismentioning
confidence: 61%
See 3 more Smart Citations
“…There was also a decrease in the oxygen content, but it was not as significant as the chlorine content, this can be attributed to the fact that the used inhibitor contains oxygen moiety that can get adsorbed on the metal surface. This proves that the used inhibitors protect the mild steel sample from the corrosive media [22,23,25].…”
Section: Edax Analysismentioning
confidence: 61%
“…From Fig ( 10c), it is observed that there is no deterioration of the mild steel coupon. This proves that the used inhibitor gets adsorbed on the metal surface and forms a protective film, thus protecting it from a corrosive solution [22,23,25].…”
Section: Sem Analysismentioning
confidence: 72%
See 2 more Smart Citations